RELIGIOUS AWARENESS DEVELOPMENT BASED ON ADULT EDUCATION FOR CORRUPTION INMATES IN PESANTREN AL-HIDAYAH CLASS I SUKAMISKIN PENITENTIARY - Lesi Oktiwanti; Ahmad Hufad; Iip Saripah (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
This research was concerned about the development of religious awareness based on adult education for corruption inmates in Pesantren Al - Hidayah. The main objective is to describe development of religious awareness process-based adult education for corruption inmates in Pesantren Al – Hidayah. The literature review of the research comprised: religious awareness, adult education, penitentiary. This research was conducted through descriptive research and case study method with a qualitative approach. Data collection techniques used through observation, interview and documentation. Subjects in this research was a spiritual adviser, Corruption inmates and tutors. The research showed that the religious awareness was applied through a participatory, fair and equitable, transparent, learning need; Multi way communication, a variety of learning methods, pragmatic, problem-based in awareness and inoculation of belief, habituation, practice and reinforcement process; spiritual adviser role as a facilitative leader. Application of self-evaluation that suitable with the ability and condition of inmates